Advances in endovascular therapy for ischemic stroke: A whole new ball game. Issue 1 (February 2016) - Law, Lai Yin; Campbell, Bruce C.V.; Wijeratne, Tissa
Abstract: Purpose of review: The burden of disability from ischemic stroke continues to intensify. Any acute therapeutic option that reduces disability after ischemic stroke should be encouraged and further studied. In particular, the need for an effective treatment in patients with large vessel occlusion has been long overdue. Recent findings: Consistent trial evidence has answered this need in an emphatic fashion, demonstrating improved functional outcomes with endovascular therapy following better patient selection, new device technology, and reduced treatment times. The article discusses the current evidence and guidelines and highlights the inherent complexities of a specialized intervention whose demand will grow exponentially. The scope for future investigation especially using advanced imaging to expand patient selection will be considered. Summary: Endovascular thrombectomy is an established and highly efficacious acute treatment for ischemic stroke that we need to apply and implement to maximize benefit to the population.